Objective assessment of dermal fibrosis in cutaneous scarring, using optical coherence tomography, high‐frequency ultrasound and immunohistomorphometry of human skin. (1st October 2019) - Ud‐Din, S.; Foden, P.; Stocking, K.; Mazhari, M.; Al‐Habba, S.; Baguneid, M.; McGeorge, D.; Bayat, A.
Summary: Background: Noninvasive quantitative assessment of dermal fibrosis remains a challenge. Optical coherence tomography (OCT) and high‐frequency ultrasound (HFUS) can accurately measure structural and physiological changes in skin. Objectives: To perform quantitative analysis of cutaneous fibrosis. Methods: Sixty‐two healthy volunteers underwent multiple sequential skin biopsies (day 0 and 1–8 weekly thereafter), with OCT and HFUS measurements at each time point supported with immunohistomorphometry analysis. Results: HFUS and OCT provided quantitative measurements of skin thickness, which increased from uninjured skin (1·18 and 1·2 mm, respectively) to week 1 (1·28 mm, P = 0·01; 1·27 mm, P = 0·02), and compared favourably with haematoxylin and eosin. Spearman correlation showed good agreement between techniques ( P < 0·001). HFUS intensity corresponded to dermal density, with reduction from uninjured skin (42%) to week 8 (29%) ( P = 0·02). The OCT attenuation coefficient linked with collagen density and was reduced at week 8 (1·43 mm, P < 0·001). Herovici analysis showed that mature collagen levels were highest in uninjured skin (72%) compared with week 8 (42%, P = 0·04). Fibronectin was greatest at week 4 (0·72 AU) and reduced at week 8 (0·56 AU); and α‐smooth muscle actin increased from uninjured skin (11·5%) to week 8 (67%, P = 0·003). Conclusions: Time‐matched comparison images between haematoxylin and eosin, OCT and HFUS demonstrated that epidermal and dermal structures were better distinguished by OCT. HFUS enabled deeper visualization of the dermis including the subcutaneous tissue. Choice of device was dependent on the depth of scar type, parameters to be measured and morphological detail required in order to provide better objective quantitative indices of the quality and extent of dermal fibrosis.